Perception of elderly related to the risk of falls and their associated factors - Bruna Soares Vasques Blaz; Rosemeiry Capriata de Souza Azevedo; Daniela Luzia Zagoto Agulhó; Annelita Almeida Oliveira Reiners; Neuber José Segri; Tiago Antônio Borges Pinheiro (Universidade Federal do Rio de Janeiro, 2020)
ABSTRACT Objective: To analyze the association of the perception of the elderly on the risk factors for falls. Methods: An Analytical cross-sectional study with 190 elderly from the Healthy Longevity Program of a public university in Mato Grosso, from May to August 2016. The collection wasdone through a structured interview and vignettes. Performed descriptive and bivariate analyzes - Pearson chi-square test (x2) significance level of 5%. The crude and adjusted prevalence ratios (PR), with confidence intervals (95%), were also estimated, followed by Poisson multiple regression. Results: Of the participants, 64.2% had a satisfactory perception about the risk factors for falls. The prevalence of unsatisfactory risk perception was 105% higher in those with income from 1 to 3 minimum wages, 75% higher in those with low risk of falls and 46% higher in those who did not attend another social group. Conclusion and implications for the practice: A significant proportion of the elderly have an unsatisfactory risk perception for the risk factors for falls associated with low income, not attending another social group and the low risk of falls. Knowledge about the risk perception of falls in the elderly helps nurses to plan and implement fall prevention programs for this population.